Molecular Mechanisms of Gene Expression Regulation in Response to Heat Stress in Hemerocallis fulva - Boyan Chu; Weixue Liu; Jinxia Li; Xiaofei Zhang; Ping Li (Plants)
Hemerocallis fulva is one of the three major flowers in the world; its flower type and color are very rich, with high ornamental value and economic value. Heat stress severely limits the cultivation and geographical distribution of H. fulva. Genetic resources and their underlying molecular mechanisms constitute the cornerstone of contemporary breeding technologies. However, research on the response of H. fulva to heat stress remains relatively scant. In this study, we used the heat-resistant ‘Dan Yang’ variety and heat-sensitive ‘Nuo Mi Lu’ variety with phenotypic expression as experimental materials to determine the changes in substance and gene expression levels, and used bioinformatics technology to study the molecular mechanisms and gene resource mining of H. fulva in response to heat stress. We identified several thousand differentially expressed genes (DEGs) in different comparison groups. At the same time, 1850 shared DEGs were identified in two H. fulva genotypes responding to heat stress. The dynamic cutting algorithm was used to cluster the genes, and 23 gene co-expression modules were obtained. The MEorangered, MElightpink, and MEmagenta modules were significantly correlated with physiological and biochemical traits. We identified ten key genes closely related to the response of H. fulva to heat stress, including plant–pathogen interactions, plant hormone signal transduction, oxidative transduction phosphorylation, and the plant hormone signal transduction pathway. This study not only analyzes the molecular mechanism of H. fulva response to heat stress, but also provides genetic resources for breeding H. fulva heat tolerance.